answersLogoWhite

0


Best Answer

Square root of 3=1 so 1+4=5

User Avatar

Wiki User

โˆ™ 2012-10-01 23:46:17
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the square root of 3x plus 4 equals 5?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you solve 8-3x equals the square root of 4xsquared plus the square root of 20 plus 8?

68


Square root of 3x plus 4 equals 2?

sqrt( 3x + 4 ) = 23x + 4 = 43x = 0x = 0Marvelous.


Can the square root of x be added to the square root of 3x?

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.


What the x value of 2x square plus 3x plus 9 equals 0?

If 2x2 + 3x + 9 = 0 then x = -0.75 - 1.984i or -0.75 + 1.984i where i is the imaginary square root of -1.


What is the square root of 8x squared plus 16 minus 3x equals 0?

the answer of √8x+16-3x=0 is x= 0.447213595 = +/- 0.447(to 3 decimal places) if I'm not mistaken


How do you factor -9x squared plus 512?

In one bracket, write 16 times the square root of 2 minus 3x. In the other one, write 16 times the square root of 2 plus 3x.


What is the answer to square root of 75x - square root of 48x?

27


What is 3x plus 5y equals 16 plus -3x -6y equals -15?

no


What are the solutions to the equation x2 plus 3x plus 3 equals 0?

x2 + 3x + 3 = 0 doesn't factor neatly. Applying the quadratic formula we find two imaginary solutions: (-3 plus or minus the square root of -3) divided by 2x = -1.5 + 0.8660254037844386ix = -1.5 - 0.8660254037844386iwhere i is the square root of negative 1


Square root 3 x-5 equals 3?

√(3x - 5) = 3 ∴3x - 5 = 9 ∴3x = 14 ∴x = 14/3


What is the solution to the following equation x2 plus 3x plus 7 equals 0?

x^2 + 3x +7 = 0 doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-3 plus or minus the square root of -19) divided by 2x = -1.5 + 2.179449471770337ix = -1.5 - 2.179449471770337iwhere i is the square root of negative 1


What is the square root of 24x to the 4th power divided by the square root of 3x?

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)


2x2 - 3x plus 7 equals 0?

2x2 - 3x + 7 = 0 doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (3 plus or minus the square root of -47) divided by 4.x = 0.75 + 1.713913650100261ix = 0.75 - 1.713913650100261iwhere i is the square root of negative 1


What is the answer to 3x plus 9?

3x plus 9 equals what?


What is 3x plus 2 equals 3x plus 6?

3x + 2 = 3x + 6 This is not possible.


3x plus 2y equals 4 -3x plus 4y equals -10?

(2, -1)


Are y equals -3x plus 2 and y plus 3x equals 4 parallel?

Their graphs are.


What is the square root of 12x?

2 root 3x


What is the square root of 9xsquared?

It is: 3x


What is the difference between y equals 3x plus 5 and 6 equals 3x plus 5?

what is a slope


2x plus 3x equals?

2x+3x = 5x


What is 4x plus 7 plus 3x equals 19 plus x?

4x plus 7 plus 3x equals 19 plus xx = 2


How do you factor the binomial 9 squared plus 25?

Assuming that's 9x2, it factors to (3x - 5i)(3x + 5i)where i is the square root of -1.


How do you factor -3ysquared plus 14-24 equals 0?

That doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (-7 plus or minus i times the square root of 23) divided by -3x = 2.3333333333333335 + -1.5986105077709063ix = 2.3333333333333335 - -1.5986105077709063iwhere i is the square root of negative 1


How do you expand the binomial three x plus four square root of five?

There is no sensible expansion of 3x + 4√5